2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--20947
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mobile Technology Impact on STEM-based Courses, Specifically Introduction to Engineering in the Era of the iPad

Abstract: received his B.S. and master's in electrical engineering from the University of Texas, El Paso, with a special focus on data communications. He is currently pursuing a Ph.D. in electrical and computer engineering. Perez has been teaching the Basic Engineering (BE) BE 1301 course for more than five years. He led the design for the development of the new BE course (now UNIV 1301) for engineering at UTEP: Engineering, Science, and University Colleges. He developed more than five new courses, including UTEP techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Since the release of the iPad, its use and suitability for the engineering and first-year engineering classroom has been studied with results disseminated through ASEE conferences. In 2012, it was reported [3] that use of the iPad in an introductory engineering course had positive impacts on the learning environment and the perceived learning impact from using the device; it was also reported that students in the iPad section maintained an academic performance on par with students in traditional sections. In 2013, at a different institution, it was found [4] that students reported high expectations and a high desire to use iPads in engineering courses, and after one semester of use, students reported a decrease in the perceived academic benefits of the iPad and a decreased interest in their continued use.…”
Section: Introductionmentioning
confidence: 99%
“…Since the release of the iPad, its use and suitability for the engineering and first-year engineering classroom has been studied with results disseminated through ASEE conferences. In 2012, it was reported [3] that use of the iPad in an introductory engineering course had positive impacts on the learning environment and the perceived learning impact from using the device; it was also reported that students in the iPad section maintained an academic performance on par with students in traditional sections. In 2013, at a different institution, it was found [4] that students reported high expectations and a high desire to use iPads in engineering courses, and after one semester of use, students reported a decrease in the perceived academic benefits of the iPad and a decreased interest in their continued use.…”
Section: Introductionmentioning
confidence: 99%